SURVEI MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN PADA SISWA KELAS XI SMA NEGERI 4 TORAJA UTARA: THE SURVEY OF STUDENT’ LEARNING MOTIVATION IN LEARNING SPORTS PHYSICAL EDUCATION AND HEALTH FOR CLASS XI STUDENTS OF SMA NEGERI 4 NORTH TORAJA - Frisillia Bannebua; Suhardianto, Suhardianto; Agus Ismail; Irfan (FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS MEGAREZKY, 2021)
This research was quantitative descriptive. The research method was a survey method. The subjects of this research were some of the students of class XI at SMA Negeri 4 Toraja. The sample were 35 students. The instrument used a questionnaire. The analysis technique used pouring frequency into percentage. The result of this research showed that students’ learning motivation in learning sports physical education and health for class XI students of SMA Negeri 4 Toraja the medium category with consideration of the highest frequency was in the medium category based on the respondents’ answer scores at intervals 0f 95-106, namely 20 students with a percentage (57%). While the other frequency distributions were in learning sport physical education and health for classXI SMA Negeri 4 North Toraja. Very poor category was 1 person with a percentage (2,86%), less category was a many as many 5 people (14,3%), moderate category was as many as 20 people (57,1%), good category was as many as 7 people ((20%), and very good category was as many as 2 people (5,7%) Penelitian ini merupakan deskriptif kuantitatif. Metode yang digunakan adalah metode survei. Subjek penelitian ini adalah sebagian siswa kelas XI di SMA Negeri 4 Toraja Utara sebanyak 35 siswa. Instrumen yang digunakan adalah angket. Teknik analisis yang digunakan adalah menuangkan frekuensi kedalam bentuk persentase. Hasil penelitian ini menunjukkan bahwa motivasi belajar siswa dalam pembelajaran pendidikan jasmani olahraga dan kesehatan pada SMA Negeri 4 Toraja Utara adalah berkategori sedang dengan pertimbangan frekuensi terbanyak berada pada kategori sedang berdasarkan skor jawaban responden pada interval 95-106 yaitu 20 siswa dengan persentase (57%). Sedangkan destribusi frekuensi yang lain dalam pembelajaran pendidikan jasmani olahraga dan kesehatan siswa kelas XI SMA Negeri 4 Toraja Utara, berkategori sangat kurang sekali 1 orang dengan persentase (2,86%) kategori kurang sebanyak 5 orang (14,3%), kategori sedang sebanyak 20 orang (57,1%), kategori baik sebanyak 7 orang (20%), baik sekali dengan sebanyak 2 orang (5,7%).